Effect of Dietary Replacement of Maize with Finger Millet (Eleusine coracana) Grain on Production Performance and Egg Quality of White Leghorn Hens - Tadele , Yilkal; Negesse, Tegene; Amha, Negassi; Yadav, K.R. (International Journal of Poultry Science, 2017)
Objective: A study was conducted to evaluate the effect of replacing maize by finger millet as energy source on feed intake, body weight gain, egg production and quality parameters of white leghorn layers. Materials and Methods: One hundred and eighty chickens were randomly distributed in 5 treatments, each replicated three times with ten layers and two cockerels/replicate in CRD and kept on a deep litter system. The treatment rations were formulated to contain finger millet in place of maize at the rate of 0 (T1), 25 (T2), 50 (T3), 75 (T4) and 100% (T5). Birds were offered a weighed amount of feed and feed leftover was collected and weighed the next morning. Weight of chicks was taken at the beginning and end of the experiment. Egg production and egg quality parameters were also recorded. Results: Finger millet contained 9% crude protein (CP) and 3280 kcal kg–1 metabolizable energy (ME) on DM basis. Dry matter intake among T1, T2, T3, T4 and T5 (94, 91, 94, 95 and 90 g/hen/day, respectively) was not different (p>0.05). There were significant differences (p<0.05) among treatments in percent hen day egg production (33.09, 34.62, 36.89, 39 and 31.96, SEM = 2.735) for T1, T2, T3, T4 and T5, respectively. Significant differences (p<0.05) among treatment groups was observed in albumen weight, shell weight and shell thickness but no significant differences (p>0.05) in yolk weight, yolk height, albumen height and haugh unit was noticed. Albumen weights of 28.2, 28.9, 29.8, 29.99 and 31 g were recorded respectively for T1, T2, T3, T4 and T5. The egg shell thickness were also 0.263, 0.298, 0.304, 0.334 and 0.314 μm for T1, T2, T3, T4 and T5, respectively. Roche color fan reading revealed that eggs from hens fed T1 diet had significantly (p<0.01) lighter yellow yolk color (1.66) than T2 (2.428), T3 (2.76), T4 (3.43) and T5 (3.33). Conclusion: Increasing dietary level of finger millet grain in layer ration has no negative impact on production performance, quality parameters of eggs and thus finger millet can completely replace maize in layers ration. Further, substitution of maize with finger millet grain up to 75% was found profitable because of the increased egg production.